The leptin receptor has no role in delta-cell control of beta-cell function in the mouse - Zhang, Jia; Katada, Kay; Mosleh, Elham; Yuhas, Andrew; Peng, Guihong; Golson, Maria L. (Frontiers in Endocrinology, 2023)
Leptin inhibits insulin secretion from isolated islets from multiple species, but the cell type that mediates this process remains elusive. Mouse models have been used to explore this question. Ablation of the leptin receptor (Lepr) throughout the pancreatic epithelium results in altered glucose homeostasis and ex vivo insulin secretion and Ca 2+ dynamics. However, Lepr removal from neither alpha nor beta cells mimics this result.LEPR is enriched in human islet delta cells. We, therefore, used a mouse model to test whether delta cells mediate the diminished glucose-stimulated insulin secretion in response to leptin. However, ablation of Lepr within mouse delta cells did not change glucose homeostasis or insulin secretion. We further show, using a publicly available scRNAseq dataset, that islet cells expressing Lepr lie within endothelial cell clusters.